1977
DOI: 10.1149/1.2133106
|View full text |Cite
|
Sign up to set email alerts
|

A Flow‐Through Porous Electrode Model: Application to Metal‐Ion Removal from Dilute Streams

Abstract: A one-dimensional model for flow-through porous electrodes operating above and below the limiting current of a metal deposition reaction has been developed. The model assumes there is one primary reactant species in an excess of supporting electrolyte and that a simultaneous side reaction may occur. The model predicts nonuniform reaction rates due to ohmic, mass-transfer, and heterogeneous kinetic limitations; the effects of axial diffusion and dispersion are included. Results are compared with the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
128
0
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 10 publications
3
128
0
1
Order By: Relevance
“…Packed bed electrodes can be used for electrochemical 25 recovery of heavy metals from a variety of industrial and 26 laboratory model solutions (Bennion and Newman, 1972;27 Doherty et al, 1996;El-Deab et al, 1999;Gaunand et al, 28 1977; Lanza and Bertazzoli, 2000;Matloz and Newman, 1986;29 Podlaha and Fenton, 1995; Ponce de León and Pletcher, 1996;30 Saleh, 2004;Soltan et al, 2003;Trainham and Newman, 1977).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Packed bed electrodes can be used for electrochemical 25 recovery of heavy metals from a variety of industrial and 26 laboratory model solutions (Bennion and Newman, 1972;27 Doherty et al, 1996;El-Deab et al, 1999;Gaunand et al, 28 1977; Lanza and Bertazzoli, 2000;Matloz and Newman, 1986;29 Podlaha and Fenton, 1995; Ponce de León and Pletcher, 1996;30 Saleh, 2004;Soltan et al, 2003;Trainham and Newman, 1977).…”
mentioning
confidence: 99%
“…Some studies have reported that flow-through configura-35 tions suffer from non-uniform potential and current distribution 36 (Bennion and Newman, 1972;Doherty et al, 1996;El-Deab 37 et al, 1999;Gaunand et al, 1977;Matloz and Newman, 1986;38 Saleh, 2004;Sioda, 1971;Trainham and Newman, 1977). The authors concluded that flow rate and bed thickness deter-46 mine the ohmic potential drop within the porous electrode.…”
mentioning
confidence: 99%
“…Planar and three-dimensional electrodes have been used for a number of reactions such as the reduction of Ag z , Cu 2z , Ni 2z and Pb 2z and their current and potential distributions have been considered elsewhere. [4][5][6][7][8][9] The successful electrodeposition of metals requires well characterised electrochemical cells where appearance, hardness and corrosion resistance of deposits can be carefully controlled. Inexpensive materials coated with a metal layer can acquire properties which are otherwise difficult and expensive to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…This avoids economic loss during treatment, and reduces both water consumption and environmental impact. Flow-through porous electrodes are usually used for electrochemical recovery of heavy metals from very dilute solutions [5][6][7][8][9][10][11]. This electrochemical reactor provides large surface area usually depleting the concentration of metal ions below 0.1 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…This last is attributed to the electrode material, shape, electrode area, and reaction mechanism (nature of the new metallic phase) involved. On the other hand, it is well known that during the depletion of the metal ions from the solutions, a potential and current distribution along the cathode occurs [5][6][7][8][9][10]. For this reason, it is highly recommendable to design thick porous electrodes with moderate flow rate of electrolyte [5][6] to avoid secondary reactions which impact in the performance of the flow through porous electrode.…”
Section: Introductionmentioning
confidence: 99%